2017
DOI: 10.1007/s00417-017-3763-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of endovascular surgery with tissue plasminogen activator injection for central retinal vein occlusion

Abstract: REVS using a specially made micro-needle may be a surgical treatment option for non-ischemic CRVO, but it did not seem effective for ischemic CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, manual cannulation of the central retinal vein has been achieved during vitrectomy. 31,32 It is technically challenging and the time of infusion is limited, which is probably why it has not been widely adopted as part of the treatment of central retinal vein occlusion. De Smet et al demonstrated that retinal vein cannulation and infusion in pig eyes was possible for up to 20 min using the PSS, an achievement unimaginable without robotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, manual cannulation of the central retinal vein has been achieved during vitrectomy. 31,32 It is technically challenging and the time of infusion is limited, which is probably why it has not been widely adopted as part of the treatment of central retinal vein occlusion. De Smet et al demonstrated that retinal vein cannulation and infusion in pig eyes was possible for up to 20 min using the PSS, an achievement unimaginable without robotics.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries that are nearly impossible with manual surgery could be realised with robotic assistance. For example, manual cannulation of the central retinal vein has been achieved during vitrectomy 31,32 . It is technically challenging and the time of infusion is limited, which is probably why it has not been widely adopted as part of the treatment of central retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that retinal endovascular surgery with injection of a tissue plasminogen activating factor (tPA) into the retinal vein for central retinal vein occlusion was effective at improving visual acuity [ 2 , 3 ]. Recently, intraretinal arterial cannulation for CRAO was shown to significantly improve visual acuity from −1.6 to −0.82 logMAR at 1 month [ 4 ].…”
Section: Introductionmentioning
confidence: 99%